Penerapan Metode Content-Based Filtering dalam Sistem Rekomendasi Video Game - Pramesti, Dewa Ayu Putri Diah; Santiyasa, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Technological developments make people very fond of playing video games, especially teenagers. Due to the increasing number of fans, video games are being produced more and more. This makes the number of video games available very large. The diversity of video games makes users feel confused about which video game they should play next, especially if some users are new to video games. Therefore, a recommender system was built to recommend video games to users by using genre as a benchmark for providing recommendations. The system will provide recommendations according to the preferences desired by the user. The method used in this research is the content-based filtering method because it can produce a fairly high precision value. In this study, the results were obtained in the form of an average precision of 87.75%.